Principals’ Interpersonal Skills, Teachers Morale and Students’ Academic Performance in Secondary Schools - Olorisade, Olayiwola; Olaoluwa, Taiwo Tolulope (JURNAL AL-TANZIM, 2024)
This study aims to evaluate the relationship between principals' interpersonal skills, teacher morale, and students' academic performance in schools in Indonesia. The method used is a quantitative approach with regression analysis to assess the simultaneous influence of the three variables. The results showed that the respondents rated the principal's interpersonal skills highly, with an average score of 2.91 (SD = 0.75). However, they did not significantly influence teacher morale (t = 0.964, p = 0.339). In contrast, teacher morals significantly influenced student academic performance, with a 29.9% increase in student performance (t = 2.241, p = 0.029). Data shows that from 2016/2017 to 2020/2021, there was a significant increase in the number of students who achieved five or more credits on the certification exam. These findings emphasize the importance of moral support for teachers in improving students' academic performance. The implication of this study is the need to develop a program that focuses on improving teacher morale to improve the quality of education and create a more productive and supportive learning environment for students.